2018
DOI: 10.1080/13543784.2018.1471132
|View full text |Cite
|
Sign up to set email alerts
|

Orlistat as a FASN inhibitor and multitargeted agent for cancer therapy

Abstract: Cancer cells have increased glycolysis and glutaminolysis. Their third feature is increased de novo lipogenesis. As such, fatty acid (FA) synthesis enzymes are over-expressed in cancer and their depletion causes antitumor effects. As fatty acid synthase (FASN) plays a pivotal role in this process, it is an attractive target for cancer therapy. Areas covered: This is a review of the lipogenic phenotype of cancer and how this phenomenon can be exploited for cancer therapy using inhibitors of FASN, with particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 139 publications
2
71
0
2
Order By: Relevance
“…Orlistat is able to irreversibly inhibit the thioesterase domain of FASN through the action of a highly reactive beta-lactone group that covalently binds the active site serine residue (Ser 2308) 41 . Studies have additionally shown that the reactive beta-lactone group of orlistat can inhibit the activity of multiple cellular enzymes 42 . Other inhibitors of FASN such as cerulenin and C-75 have similar off target effects 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Orlistat is able to irreversibly inhibit the thioesterase domain of FASN through the action of a highly reactive beta-lactone group that covalently binds the active site serine residue (Ser 2308) 41 . Studies have additionally shown that the reactive beta-lactone group of orlistat can inhibit the activity of multiple cellular enzymes 42 . Other inhibitors of FASN such as cerulenin and C-75 have similar off target effects 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Orlistat and other FASN inhibitors have previously been examined for their anti-cancer and antiviral activities. Although the clinically approved oral administration of Orlistat does not result in its significant systemic distribution, pre-clinical studies in mice have demonstrated that systemic administration of Orlistat is well tolerated 47 .…”
Section: Vps34mentioning
confidence: 99%
“…Finally, fatty acid synthase (FASN) protein, a multifunctional enzyme that plays a central role in lipid synthesis, is particularly noteworthy in regard to glioma. This enzyme is often deregulated in several types of cancer [14] including GBM, in which its overexpression correlates with a more advanced disease stage [15]. FASN is also strongly expressed in patients with glioma stem cells (GSCs) and its inhibition reduces the expression of stem cell markers in favor of differentiation markers in GSCs [16].…”
Section: Introductionmentioning
confidence: 99%